Microbiota of coal pit waste heaps of Chervonograd Mining Region after coal ash application - S. V. Kuzmishyna; S. O. Hnatush; A. A. Halushka (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2015)
The aim of this work was to determine the impact of addition of coal ash from Dobrotvir TPP to waste heaps gangue (Chervonograd Mining Region) on the number of different groups of microorganisms. 20 samples from three waste heaps, from the black and red gangue, under the mosses and from bare substrate and also from terrace, top and base of each waste heap, were selected. Waste heaps gangues with coal ash from Dobrotir TPP were mixed in vitro and left for 10 days. We used proportion of coal ash to gangue as 1 to 5. Microorganisms were grown in Petri dishes containing 20–30 ml agar medium and in 22 ml tubes at temperature of 28 °C. Microscopic fungi were revealed on Mash-agar; oligonitrophilic bacteria – on Ashby medium; actinomycetes – on Chapek’s medium; cellulose decomposing aerobic bacteria – on Hetchenson medium; colorless sulfur oxidizing bacteria: neutrophilic – on Beyerinck medium, acidophilic – on Silverman and Lundgren 9К medium. The acidity value of waste heaps gangue samples was determined by рН meter рН-150М. We observed that samples collected under the mosses had lower acidity compared to samples from the bare substrate. We also revealed lower acidity of the overburn red gangue than the acidity of freshly deposited black gangue. To sum up, application of coal ash resulted in lowering of acidity value among all samples under study. Coal ash addition led to increase in number of microscopic fungi cells compared to the appropriate control samples. The highest quantity of microscopic fungi (16.2 ± 0.79) х 105 CFU/g of gangue) was revealed in sample from red rock of the main waste heap of Central Enrichment Plant (CEP). At the same time, we observed the highest cell number in the control sample under the mosses of “Nadija” coal pit waste heap, (6.1 ± 0.3) х 105 CFU/g of gangue. After coal ash addition, most samples featured 2–3 times higher quantities of colorless sulfur-oxidizing neutrophilic bacteria cells. The highest cell number of these microorganisms was observed in sample under the mosses of “Vizejska” coal pit waste heap. The same dominance of oligonitrophilic bacteria cell number in experimental samples over control samples was indicated. The highest cell quantity was recorded for the sample under the moss from terrace of waste heap of “Nadija” coal pit (25.6 ± 1.3) х 104 CFU/g of gangue and in sample from red rock of CEP main waste heap (21.1 ± 1.1) х 104 CFU/g of gangue, being 43.3 and 31.7 times higher than the appropriate controls. Meanwhile, the number of colorless sulfur-oxidizing acidophilic bacteria in control samples was higher than that after coal ash addition, particularly, on the bare substrate samples from the base and terrace of waste heap of “Nadija” coal pit. Higher cell number in control samples without coal ash was typical for actinomycetes with the greatest difference (8.6 times) before and after coal ash addition in a sample from red rock of CEP main waste heap. We detected 2 times lower number of cellulose-decomposing aerobic bacteria in the majority of experimental samples compared to appropriate control samples under study. In that way, we noticed that addition of coal ash from Dobrotvir TPP to waste heaps gangue (in proportion of coal ash to gangue as 1 to 5) caused reduction of substrate acidity value. Under these conditions the number of colorless sulfur-oxidizing neutrophilic bacteria, oligonitrophilic bacteria and microscopic fungi cells increased. But on the other hand, coal ash addition resulted in lowering of the number of colorless sulfur-oxidizing acidophilic bacteria, actinomycetes, and cellulose-decomposing aerobic bacteria cells.